Potential and methods of wireless communications for Internet of things based on UAV - Qingheng SONG; Fuchun ZHENG (物联网学报)
In the absence of terrestrial infrastructure for Internet of things (IoT),an effective low-cost wireless connection can be provided by an unmanned aerial vehicle (UAV) based wireless communication platform.Compared with the terrestrial IoT communication platform,the low-altitude UAV wireless communication system enjoys the advantage of rapid deployment,low cost,on-demand deployment,flexible configuration and better communication channel quality due to short-range line-of-sight links.On the other hand,several new challenges must be overcome due to the high mobility and energy consumption limitations of UAV.An overview of UAV enabled IoT wireless communication was provided,including the air-to-ground channel model,the power consumption model,as well as the applications in UAV based data dissemination/collection and relay,with particular reference to the new opportunities and solutions in these application areas.